HLA-DRB1*14 is a protective allele for multiple sclerosis in an admixed Colombian population. Issue 1 (February 2016) - Toro, Jaime; Cuellar-Giraldo, David; Díaz-Cruz, Camilo; Burbano, Lisseth-Estefania; Guío, Claudia-Marcela; Reyes, Saúl; Cortes, Fabián; Cárdenas-Robledo, Simón; Narváez, Diana M.; Cárdenas, Wilmer; Porras, Alexandra; Lattig, María-Claudia; et al.
Abstract : Objective: The aim of this study was to determine ancestry informative markers, mitochondrial DNA haplogroups, and the association between HLA-DRB1 alleles and multiple sclerosis (MS) in a group of patients from Bogotá, Colombia. Methods: In this case-control study, genomic DNA was isolated and purified from blood samples. HLA-DRB1 allele genotyping was done using PCR. Mitochondrial hypervariable region 1 was amplified and haplogroups were determined using HaploGrep software. Genomic ancestry was estimated by genotyping a panel of ancestry informative markers. To test the association of HLA polymorphisms and MS, we ran separate multivariate logistic regression models. Bonferroni correction was used to account for multiple regression tests. Results: A total of 100 patients with MS (mean age 40.4 ± 12 years; 70% females) and 200 healthy controls (mean age 37.6 ± 11 years; 83.5% females) were included in the analysis. Ancestry proportions and haplogroup frequencies did not differ between patients and controls. HLA-DRB1*15 was present in 31% of cases and 13.5% of controls, whereas HLA-DRB1*14 was present in 5% of cases and 15.5% of controls. In the multivariate model, HLA-DRB1*15 was significantly associated with MS (odds ratio [OR] = 3.05, p < 0.001), whereas HLA-DRB1*14 was confirmed as a protective factor in our population (OR = 0.16, p = 0.001). Conclusions: This study provides evidence indicating that HLA-DRB1*15 allele confers susceptibility to MS and HLA-DRB1*14 allele exerts resistance to MS in a highly admixed population. This latter finding could partially explain the low prevalence of MS in Bogotá, Colombia.